Haemodynamic Monitoring Using Echocardiography in the Critically Ill: A Review - Michelle S. Chew (Cardiology Research and Practice)
Physicians caring for the critically ill are now expected to acquire competence in echocardiography. It has become an indispensable diagnostic and monitoring tool in acute care settings where it is generally accepted to have therapeutic impact. There are a number of indications for a critical care echocardiographic study, and the most important queries include those pertaining left and right ventricular function and filling status. Focused examinations are increasing in popularity and provide a means for systematic study, and can be easily learned and practiced by novices. This paper addresses the indications, therapeutic impact, and some of the most common questions that can be answered using echocardiography the in critically ill patient.